Pengaruh Kualitas Produk, Citra Merek, dan Promosi Terhadap Kepuasan Pelanggan Di Kopi Kenangan Ruko MOI - Ade wira Surya pangestu; Meylani Tuti (Human Capital Development, 2022)
The purpose of this study was to determine the effect of product quality, brand image, and promotion on customer satisfaction at Kopi Kenangan Ruko Mall Of Indonesia. The population of this study are consumers who have made more than one purchase. and the sampling technique used is purposive sampling. The sample size is 85 respondents. The data analysis method in this study uses multiple regression analysis using the SPSS 24 program. The results of this study include product quality, brand image, and promotions have a positive and significant impact on customer satisfaction Kopi Kenangan Ruko Mall Of Indonesia. Keywords: product quality, brand image, promotion, customer satisfaction